Analysis of The Circular Model of SOME in The Publication of PTPN XI Surabaya Activities through Instagram - Zakiyah, Alfina Rizkyana; Nofandrilla, Nieldya (Universitas Muhammadiyah Surakarta, 2022)
Purpose: The purpose of this study was to find out the role of public relations in publicizing company activities at PT Perkebunan Nusantara XI Surabaya through social media platform such as Instagram. Methodology: The method used in this research is qualitative method with purposive sampling technique. Result: The results showed that in the Share stage, PTPN XI's public relations chose Instagram as a media for informations because it has a wide distribution and is able to accommodate audio-visual contents. Optimize, PTPN XI's public relations team plans the concept or content for Instagram. Manage, Stages of monitoring, PTPN XI's public relations company monitors, evaluates, manages feedback on posts, likes, and insights. Engage, the closeness stage of PTPN XI's company and audience uses the greeting #elevenia to greet followers or audience in content and captions. Application/Originality/Value: This study, compared to the previous research, examines PTPN XI's Instagram activities more deeply using the SOME model analysis. The differences in this research are the object of research, the analysis of the theory used, the measuring instruments, and the literatures in the research.